GENERAL QUESTIONS REGARDING THE PREPARATION OF THE STATE BORDER PROTECTION BODY FOR ACTIONS IN THE NEXT PERIOD OF STATE BORDER PROTECTION - Korchev, Volodymyr; Morozov, Ihor (Honor and Law, 2023)
Protection of the state border of Ukraine is a part and parcel of the state system of ensuring national security. The border detachment as a territorial body in the State Border Service of Ukraine, in accordance with its competence, performs the tasks of ensuring the security of the state border, preventing crimes and administrative offenses related to illegal activities at the state border. The objective need for the effective implementation of the state policy in the sphere of the security of the state border of Ukraine puts forth demands for the further development of scientific approaches to the work of the management bodies of the border detachment in preparation for operational and service activities both in terms of everyday activities and in terms of worsening of the situation at the state border. Considering the current problem that exists today in the course of preparing a border guard detachment for operational and service activity in the next period, the article summarizes the categories of management, management activity. The author defines the notion of preparation for operational and service activities and reveals its structure and content. Preparation of a body (unit) for action is a set of measures aimed at bringing the body (unit) into a state which ensures the fulfilment of the task, direct training of forces and means for protection of the State border, terrain and control over the readiness of the body (unit). It includes planning of actions; organisation of actions; direct preparation of the body (unit) for actions; control of the body’s (unit’s) readiness for actions. The analysis made it possible to identify several important provisions that define the essence of management, namely: purposeful activity; presence of a subject and an object of management; implementation of managerial influence. The managerial activity of the head (commander) of the state border guard agency (unit) includes several stages: the work of the management bodies to maintain the agency’s (unit’s) readiness for action (carried out on a regular basis); preparation of the agency (unit) for action and management of the agency (unit) while performing the task (operational management). Taken in its integrity, management activities should ensure progressive development, the transition from lower to higher forms of activity.